2015
DOI: 10.5194/nhess-15-1493-2015
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the selection of tsunami human vulnerability indicators: conclusions from tsunami impacts in Sri Lanka and Thailand (2004), Samoa (2009), Chile (2010) and Japan (2011)

Abstract: Abstract. After several tsunami events with disastrous consequences around the world, coastal countries have realized the need to be prepared to minimize human mortality and damage to coastal infrastructures, livelihoods and resources. The international scientific community is striving to develop and validate methodologies for tsunami hazard and vulnerability and risk assessments. The vulnerability of coastal communities is usually assessed through the definition of sets of indicators based on previous literat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In line with this, Løvholt et al (2014, p. 133) point out that studies of the impact of the 2004 Indian Ocean tsunami show that "in Sri Lanka, people within the 100-m zone from the shoreline were more likely to die and to be seriously injured than people living outside this zone". In turn, González-Riancho et al (2015) underline that 72 % of the housing units within the 200 m line from the shoreline in Sri Lanka were completely or partially damaged, leading to a higher number of victims. Eckert et al (2012) also point out that buildings within that area are highly vulnerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, Løvholt et al (2014, p. 133) point out that studies of the impact of the 2004 Indian Ocean tsunami show that "in Sri Lanka, people within the 100-m zone from the shoreline were more likely to die and to be seriously injured than people living outside this zone". In turn, González-Riancho et al (2015) underline that 72 % of the housing units within the 200 m line from the shoreline in Sri Lanka were completely or partially damaged, leading to a higher number of victims. Eckert et al (2012) also point out that buildings within that area are highly vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Authors like Birkmann (2006) and Frazier et al (2014) stress the need for strengthening and focus risk mitigation and adaptation plans through the spatial assessment of hazard, vulnerability, and exposure factors. In line with this, based on thorough analyses of previous tsunami disaster outcomes (including the 2011 Great East Japan Earthquake and Tsunami, the 2010 Chilean tsunami, the 2009 Samoan tsunami, and the 2004 Indian Ocean tsunami) or pre-disaster modelling, scholars like Anwar et al (2011), Birkmann et al (2010), Eckert et al (2012), González-Riancho et al (2015), Suppasri et al (2016), and Zamora et al (2021) have underlined a range of characteristics leading to tsunami risk (with a focus on either the population or the built environment). These aspects comprise determinants of hazard (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…These short times severely constrain the response of the population exposed to this hazard, where school-age children (i.e., persons aged 18 and younger) are particularly vulnerable, due to several reasons. It has been shown that very young populations have higher mortality rates in tsunamis as the result of difficulties related to reduced mobility and low pedestrian velocity that compromise their evacuation capacities (Birkmann et al, 2010;González-Riancho et al, 2015;Yun and Hamada, 2015;Latcharote et al, 2018). Buchmüller and Weidmann (2006) estimated that kids age five and under walk at an average speed of roughly 0.6 (meters/second), which is less than 40% of that of a person in his/her late teens.…”
Section: Introductionmentioning
confidence: 99%
“…Tsunami hazard and risk assessments provide crucial decision-support tools to inform disaster resilience in coastal locations, particularly in the context of preparedness, evacuation and land-use planning [1][2][3][4][5][6]. Indeed, with global tsunami-related casualties and damages estimated to be one hundred times greater between 1998 and 2017 compared to the preceding 20 year period, due largely to the 2004 Indian Ocean and 2011 Tohoku-oki tsunamis [7], the need for hazard risk information in tsunami-prone regions is essential (e.g., [8,9]).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of built elements, particularly buildings and roads for example, provide useful indicators for population clusters (e.g., [19]). Building and road exposure to the physical characteristics of tsunamis (e.g., flow depth, extent, distance from coast, shielding) can support the identification of vulnerable clusters or 'risk hotspots' (e.g., [8]), whereby mitigation and risk reduction strategies could be targeted (e.g., identifying compromised structures and routes where evacuation might be impeded).…”
Section: Introductionmentioning
confidence: 99%